Molecular detection of human parasitic pathogens - Liu, Dongyou (Boca Raton : CRC Press, 2013)
'A book on the molecular detection of major human viral, bacterial, fungal, and parasitic pathogens, this text provides coverage of the organisms with an emphasis on the sample preparation and molecular detection procedures. Chapters consist of concise reviews of pathogens in respect to taxonomy, biology, epidemiology, and pathogenesis; a description of a clinical sample collection preparation procedures; a summary of molecular detection methods available; and a discussion on the challenges, limitations, and advantages for current methods. Written for practitioners and students, this textbook is a guide for future development of improved molecular methods for pathogens. Offers an in-depth review of state-of-the-art molecular detection and identification methods for human parasitic pathogens. Provides comprehensive coverage of important human parasitic pathogens. Provides an authoritative summary of biology, epidemiology, and pathogenesis of major human parasitic pathogens. Includes chapter entries written by experts in respective fields of human parasitic pathogen collection'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Molecular parasitology; Parasitic Diseases -- microbiology; Parasitic diseases -- Molecular diagnosis